Adopting Behavior-Driven Development (BDD) in software development: a multivocal review - Richarlison Ribeiro dos Santos, Shexmo (2024)
Context: In Software Development, it is essential to use frameworks that can help achieve the goal regarding the behavior expected by the system. Problem: Identify the point of view of researchers and professionals regarding the Behavior-Driven Development (BDD) agile framework. Solution: Characterize the BDD framework through a Multivocal Literature Review (MLR). Method: We performed an MLR in the central databases of white and gray literature. Summarization of Results: We identified the main aspects related to the adoption of BDD to characterize its adoption. Contributions and Impact: Through this study, it was possible to advance the understanding of the adoption of BDD to contribute to the scientific community and industry on the aspects inherent to the application of this framework.